2017
DOI: 10.3390/ijms18081625
|View full text |Cite
|
Sign up to set email alerts
|

High Salt Tolerance of a Bradyrhizobium Strain and Its Promotion of the Growth of Stylosanthes guianensis

Abstract: Salinity is a serious limiting factor for the growth of rhizobia. Some rhizobia are tolerant to salt stress and promote plant growth, but the mechanisms underlying these effects are poorly characterized. The growth responses and osmoprotectants in four Bradyrhizobium strains were examined under salt stress in this study. Two-dimensional electrophoresis (2-DE) and mass spectrometry were conducted to investigate protein profiles in rhizobia exposed to salt stress. Subsequently, salt tolerance in stylo (Stylosant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…However, ESA 379, ESA 368, ESA 381, ESA 384, and ESA 372, which were isolated from the same land use area (UNEB), showed different behavior under NaCl stress conditions. Within this area, the best performances were found for isolates ESA 379 and ESA 368, indicating that despite originating from the same agricultural system, they exhibited different behavior under stress, corroborant to the hypothesis that the salt stress tolerance is a result of the specific characteristics of each isolate (Dong et al 2017).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, ESA 379, ESA 368, ESA 381, ESA 384, and ESA 372, which were isolated from the same land use area (UNEB), showed different behavior under NaCl stress conditions. Within this area, the best performances were found for isolates ESA 379 and ESA 368, indicating that despite originating from the same agricultural system, they exhibited different behavior under stress, corroborant to the hypothesis that the salt stress tolerance is a result of the specific characteristics of each isolate (Dong et al 2017).…”
Section: Discussionsupporting
confidence: 76%
“…The results of this study do not indicate that there is a direct link between the use of the soil from which the bacteria were isolated and the tolerance of these isolates to salt stress isolates ESA 388, ESA 379, ESA 365, and BR 3267 showed lower growth reduction under salt stress, demonstrating increased adaptability to salt stress. Rhizobia with higher tolerance to salt stress may exhibit greater symbiotic efficiency under stress conditions (Dong et al 2017). But negative correlations between growth promotion and salt stress tolerance for plant growth-promoting bacteria of non-legumes (de Lima et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Bradyrhizobium strains are among the most sensitive to a high-salt environment followed by Mesorhizobium, while Rhizobium and Sinorhizobium are relatively more tolerant (Laranjo and Oliveira, 2011;Brígido et al, 2012). The increased concentration of low molecular weight solutes is one of the several mechanisms observed in salt-tolerant strains (Dong et al, 2017;Furlan et al, 2017). To increase the biosynthesis of trehalose, the M. ciceri strain was modified to improve tolerance to salt as well as symbiosis with the host (Moussaid et al, 2015).…”
Section: Salinitymentioning
confidence: 99%
“…In the current study, we observed that increasing salt stress had little negative impact on root nodulation index, which could be partly explained by the salt tolerance of this rhizobium strain [9]. Inoculation of the pasture legume Stylosanthes guianensis with several strains of Rhizobium showed that root nodulation was not affected even under a 300 mM NaCl stress when this forage legume was inoculated with a salt-tolerant strain [34]. The rhizobium strain used in our experiment was able to infect and nodulate alfalfa under a severe salt stress of 160 mM NaCl, confirming the salt tolerance of that strain.…”
Section: Biomass and Relative Water Contentmentioning
confidence: 46%
“…The use of a salt-tolerant rhizobium strain could have further helped to maintain the root water balance [32]. Rhizobia can increase alfalfa salt tolerance through various mechanisms, including the prevention of excessive sodium uptake to maintain ionic balance in roots and leaves [33] and production of osmoprotective compounds [34]. It has, however, been reported that a high salinity level may negatively affect the nodulation capacity by the inhibition of initial steps of the establishment of Rhizobium-legume symbiosis [24,35].…”
Section: Biomass and Relative Water Contentmentioning
confidence: 99%